IGF-I increases markers of osteoblastic activity and reduces bone resorption via osteoprotegerin and RANK-ligand - Guerra-Menéndez, Lucia (J Transl Med, 2013)
BACKGROUND: Bone is one of the major target tissues for Insulin-like Growth Factor I (IGF-I). Low doses of IGF-I were able to improve liver-associated osteopenia. In the present work, a model of partial IGF-I deficiency was used in order to provide insight into the mechanisms of the beneficial actions of IGF-I replacement therapy in bone. METHODS: Several proteins involved in osteoblastic/osteocyte and osteoclastic differentiation and activity were studied in the three experimental groups: control (CO) group (wild type mice, Igf(+/+), n = 10), heterozygous Igf(+/-) group with partial IGF-I deficiency (Hz, n = 10), and heterozygous Igf(+/-) mice treated with IGF-I for 10 days (Hz + IGF-I, n = 10). RESULTS: Data in this paper confirm that the simple partial IGF-I deficiency is responsible for osteopenia, determined by densitometry and histopathology. These findings are associated with a reduced gene expression of osteoprotegerin, sclerostin, calcitonin receptor (CTR), insulin-like growth factor binding protein 5 and RUNX2. IGF-I replacement therapy normalized CTR gene expression and reduced markers of osteoclastic activity. CONCLUSIONS: Low doses of IGF-I constituted a real replacement therapy that normalized IGF-I serum levels improving the expression of most of these proteins closely involved in bone-forming, and reducing bone resorption by mechanisms related to osteoprotegerin, RANKL and PTH receptor.